Coagulation Testing in Acute Ischemic Stroke Patients Taking Non–Vitamin K Antagonist Oral Anticoagulants. Issue 1 (January 2017) - Purrucker, Jan C.; Haas, Kirsten; Rizos, Timolaos; Khan, Shujah; Poli, Sven; Kraft, Peter; Kleinschnitz, Christoph; Dziewas, Rainer; Binder, Andreas; Palm, Frederick; Jander, Sebastian; Soda, Hassan; et al.
Abstract : Background and Purpose—: In patients who present with acute ischemic stroke while on treatment with non–vitamin K antagonist oral anticoagulants (NOACs), coagulation testing is necessary to confirm the eligibility for thrombolytic therapy. We evaluated the current use of coagulation testing in routine clinical practice in patients who were on NOAC treatment at the time of acute ischemic stroke. Methods—: Prospective multicenter observational RASUNOA registry (Registry of Acute Stroke Under New Oral Anticoagulants; February 2012–2015). Results of locally performed nonspecific (international normalized ratio, activated partial thromboplastin time, and thrombin time) and specific (antifactor Xa tests, hemoclot assay) coagulation tests were documented. The implications of test results for thrombolysis decision-making were explored. Results—: In the 290 patients enrolled, nonspecific coagulation tests were performed in ≥95% and specific coagulation tests in 26.9% of patients. Normal values of activated partial thromboplastin time and international normalized ratio did not reliably rule out peak drug levels at the time of the diagnostic tests (false-negative rates 11%–44% [95% confidence interval 1%–69%]). Twelve percent of patients apparently failed to take the prescribed NOAC prior to the acute event. Only 5.7% (9/159) of patients in the 4.5-hour time window received thrombolysis, and NOAC treatment was documented as main reason for not administering thrombolysis in 52.7% (79/150) of patients. Conclusions—: NOAC treatment currently poses a significant barrier to thrombolysis in ischemic stroke. Because nonspecific coagulation test results within normal range have a high false-negative rate for detection of relevant drug concentrations, rapid drug-specific tests for thrombolysis decision-making should be established. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01850797. Abstract : Supplemental Digital Content is available in the text.